2020
DOI: 10.1111/eth.13103
|View full text |Cite
|
Sign up to set email alerts
|

No behavioral syndromes or sex‐specific personality differences in the southern rainforest sunskink (Lampropholis similis)

Abstract: Behavioral syndromes, when individuals within a population express consistent behavioral differences across time and context, are widespread in animal taxa. For many species, males and females experience different selective pressures after maturation, resulting in the divergence of life‐history and behavioral traits. However, the potential for sex‐specific differences in individual behaviors and behavioral syndromes has rarely been assessed. Here, we tested for sex‐specific differences in behavior (activity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Overall, differences in repeatability because of variation in developmental environment were primarily driven by changes in within-individual variation, which were higher in a greater number of traits for the high incubation treatment and lowest in the wild-caught group. We also found no evidence for a behavioral syndrome involving these behaviors in rainforest sunskinks, similar to previous studies on this species (Goulet et al 2021), indicating that incubation temperature, as well as rearing in a captive compared to wild environment, does not affect between-individual correlations among behavioral traits. While our results further highlight the lasting effects of developmental conditions on an organism's phenotype via behavioral responses, the fitness and ecological consequences of these effects remain unclear.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, differences in repeatability because of variation in developmental environment were primarily driven by changes in within-individual variation, which were higher in a greater number of traits for the high incubation treatment and lowest in the wild-caught group. We also found no evidence for a behavioral syndrome involving these behaviors in rainforest sunskinks, similar to previous studies on this species (Goulet et al 2021), indicating that incubation temperature, as well as rearing in a captive compared to wild environment, does not affect between-individual correlations among behavioral traits. While our results further highlight the lasting effects of developmental conditions on an organism's phenotype via behavioral responses, the fitness and ecological consequences of these effects remain unclear.…”
Section: Discussionsupporting
confidence: 90%
“…In this species, incubation temperature was found to affect dessication rate and short-term critical thermal minima (Llewelyn et al 2018), but effects of incubation temperature on behavior have not yet been investigated. Furthermore, while no behavioral syndrome has yet been found in captive-reared southern rainforest sunskinks (Goulet et al 2021), previous studies have suggested that natural environments may be necessary to generate and maintain repeatability in, and correlations between, behavioral traits (Wilson et al 1994;Urszan et al 2015). As such, a secondary aim of our study was to investigate if skinks that had developed in captivity differed in animal personality from those that had developed in the wild.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently several studies have also compared syndrome structure among sexes with mixed results. Some studies reported large differences in behavioral syndromes between males and females (Fresneau et al 2014;Han et al 2015;Way et al 2015) while others support a conserved syndrome structure between sexes (Michelangeli et al 2016;Goulet et al 2021). Our results supply an additional line of evidence in favor of sex-specific syndromes.…”
Section: Discussionsupporting
confidence: 74%